Erlotinib 150 mg daily plus chemotherapy in advanced pancreatic cancer: an interim safety analysis of a multicenter, randomized, cross-over phase III trial of the "Arbeitsgemeinschaft Internistische Onkologie" - Böck, Stefan; Vehling-Kaiser, Ursula; Waldschmidt, Dirk; Kettner, Erika; Märten, Angela; Winkelmann, Cornelia; Klein, Stefan; Kojouharoff, Georgi; Gauler, Thomas; Fischer von Weikersthal, Ludwig; Clemens, Michael R.; Geißler, Michael; et al. (Anti-cancer drugs, 2010)
To date, only limited toxicity data are available for the combination of erlotinib with either capecitabine or gemcitabine as front-line therapy for advanced pancreatic cancer. Within a randomized phase III trial, 281 treatment-naive patients were randomly assigned between capecitabine (2000 mg/m2/day, for 14 days, once every 3 weeks) plus erlotinib (150 mg/day, arm A) and gemcitabine (1000 mg/m2 as a 30-min infusion) plus erlotinib (150 mg/day, arm B). In case of treatment failure, patients were crossed over to a second-line treatment with the comparator cytostatic drug without erlotinib. The primary study endpoint was the time to treatment failure of second-line therapy (TTF2). This interim analysis of toxicity contains safety data from the first 127 randomized patients. During first-line therapy, patients received a median number of three treatment cycles (range 0-13) in both the arms. Regarding chemotherapy, a treatment delay was observed in 12% of the cycles in arm A and in 22% of the cycles in arm B. Dose reductions of the cytostatic drug were performed in 18 and 27% of treatment cycles, respectively. Erlotinib dose reductions were performed in 6 and 11% of all cycles. Grade 3/4 hematological toxicity was <10% in both the arms; major grade 3/4 toxicities in arms A and B were diarrhea (9 vs. 7%), skin rash (4 vs. 12%), and hand-foot syndrome (7 vs. 0%). No treatment-related death was observed. In conclusion, this interim safety analysis suggests that treatment with erlotinib 150 mg/day is feasible in combination with capecitabine or gemcitabine.